Corrosion study on AA-TIG welding of duplex stainless steel. (2021) - Sasikumar, C.; Sundaresan, R.; Merlin Medona, C.; Ramakrishnan, A.
Abstract: Duplex Stainless steel composition has high amounts of Cr, Ni, Mo and Fe content. Due to the high chromium content passive layer of chromium precipitate is formed on the surface of the material which resists the corrosion in the metal. Duplex Stainless steel (DSS) has good weldability and formability. Based on previous Investigations found through various literatures there is no detailed investigation was carried out on the corrosion behaviour of Automated Autogenous Tungsten Inert Gas (AA-TIG) Welding on Duplex stainless steel. To study the corrosion behaviour of Duplex Stainless Steel, This investigation was carried out in Sodium chloride (NaCl) solution environment. The main objective is to study the corrosion behaviour of the welded material by using PARSTAT 2273. To study the electrochemical impedance technique was chosen to test the AA-TIG welded DSS 2205.